2019
DOI: 10.1128/aem.00077-19
|View full text |Cite
|
Sign up to set email alerts
|

An Osmoregulatory Mechanism Operating through OmpR and LrhA Controls the Motile-Sessile Switch in the Plant Growth-Promoting Bacterium Pantoea alhagi

Abstract: Adaptation to osmotic stress is crucial for bacterial growth and survival in changing environments. Although a large number of osmotic stress response genes have been identified in various bacterial species, how osmotic changes affect bacterial motility, biofilm formation, and colonization of host niches remains largely unknown. In this study, we report that the LrhA regulator is an osmoregulated transcription factor that directly binds to the promoters of the flhDC, eps, and opgGH operons and differentially r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 83 publications
(128 reference statements)
0
7
0
Order By: Relevance
“…A recent study showed that Pantoea alhagi senses environmental osmolarity changes through the EnvZ/OmpR system and LrhA to regulate synthesis of OPGs, EPS production and flagella-dependent motility. OPGs control the Rcs activation in a concentrationdependent manner, and a high concentration of OPGs induced by increased medium osmolarity is maintained to achieve the high level of activation of the Rcs phosphorelay which results in enhanced EPS synthesis and decreased motility in P. alhagi (Li et al, 2019). As motility and biofilm formation are critical for bacterial colonization of the host, these findings indicate that OPGs associated with Rcs and EnvZ/OmpR systems play a key role in shaping the pathogenic phenotype of bacteria.…”
Section: Discussionmentioning
confidence: 91%
“…A recent study showed that Pantoea alhagi senses environmental osmolarity changes through the EnvZ/OmpR system and LrhA to regulate synthesis of OPGs, EPS production and flagella-dependent motility. OPGs control the Rcs activation in a concentrationdependent manner, and a high concentration of OPGs induced by increased medium osmolarity is maintained to achieve the high level of activation of the Rcs phosphorelay which results in enhanced EPS synthesis and decreased motility in P. alhagi (Li et al, 2019). As motility and biofilm formation are critical for bacterial colonization of the host, these findings indicate that OPGs associated with Rcs and EnvZ/OmpR systems play a key role in shaping the pathogenic phenotype of bacteria.…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, nearly 60% of genes with COG assigned to that class were repressed upon stress. Hyperosmotic stresses have already been shown to repress motility gene transcription in many bacteria [32][33][34][35][36] including rhizobia [37]. Interestingly the repression of motility is often associated to an induction of genes involved in the synthesis of biofilm components such as surface polysaccharides or proteins [32,35,38,39].…”
Section: Resultsmentioning
confidence: 99%
“…The similarities in phenotypes could indicate both genes influence biofilms in a similar manner. The role of lrhA in motility regulation has been well documented [43,44,73], and expression of tomB has been seen to reduce motility through repression of fliA [74]. Although ΔlrhA and ΔtomB deletion mutation strains shared many similar phenotypes, TraDIS-Xpress data predicted that tomB was beneficial and lrhA was detrimental to biofilm development at 12, 24 and 48 h. Therefore, these genes may regulate the same pathways but in different ways.…”
Section: Discussionmentioning
confidence: 99%